2018
DOI: 10.1161/circulationaha.117.032094
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Interatrial Shunt Device for the Treatment of Heart Failure With Preserved Ejection Fraction (REDUCE LAP-HF I [Reduce Elevated Left Atrial Pressure in Patients With Heart Failure])

Abstract: Background: In nonrandomized, open-label studies, a transcatheter interatrial shunt device (IASD, Corvia Medical) was associated with lower pulmonary capillary wedge pressure (PCWP), fewer symptoms, and greater quality of life and exercise capacity in patients with heart failure (HF) and midrange or preserved ejection fraction (EF ≥40%). We conducted the first randomized sham-controlled trial to evaluate the IASD in HF with EF ≥40%. Methods: REDUCE LAP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 29 publications
4
168
1
4
Order By: Relevance
“…Recent studies reported early clinical and haemodynamic benefits of a transcatheter interatrial shunt device designed to reduce left atrial pressure in patients with heart failure, irrespective of LVEF 21 22. The transcatheter interatrial shunt device reduced PCWP during exercise in patients with heart failure with preserved LVEF21 and have shown improvements in NYHA classification, quality of life, 6 min walk test distance and PCWP with no changes in RAP and PAP in patients with heart failure with reduced LVEF 22. In the present study, even though LVEF at 12 months was significantly lower and mean PAP by the catheter after the procedure and the prevalence of MR ≥3+ at 12 months were significantly higher in patients with 12M-iASD than in patients without 12M-iASD, Doppler estimated systolic PAP in patients with 12M-iASD dramatically decreased and became similar to those in patients without 12M-iASD at 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported early clinical and haemodynamic benefits of a transcatheter interatrial shunt device designed to reduce left atrial pressure in patients with heart failure, irrespective of LVEF 21 22. The transcatheter interatrial shunt device reduced PCWP during exercise in patients with heart failure with preserved LVEF21 and have shown improvements in NYHA classification, quality of life, 6 min walk test distance and PCWP with no changes in RAP and PAP in patients with heart failure with reduced LVEF 22. In the present study, even though LVEF at 12 months was significantly lower and mean PAP by the catheter after the procedure and the prevalence of MR ≥3+ at 12 months were significantly higher in patients with 12M-iASD than in patients without 12M-iASD, Doppler estimated systolic PAP in patients with 12M-iASD dramatically decreased and became similar to those in patients without 12M-iASD at 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…93 The Reduce Elevated Left Atrial Pressure in Patients With Heart Failure (REDUCE LAP-HF I) Trial is a prospective, randomized, sham-controlled clinical trial evaluating a novel interatrial shunt device (IASD) in patients with HFpEF and offers a non-pharmacologic approach to unload the left atrium without compromising LV filling or output. 94 This phase II study has recently finished enrollment, and previous unblinded, single-arm studies have demonstrated promising results for safety and efficacy. 95, 96 …”
Section: Novel Pharmacological Agents For the Treatment Of Hfpefmentioning
confidence: 99%
“…94, 109, 110 These underlying pathogenic factors affect other organs, leading to pulmonary hypertension, skeletal muscle weakness, and sodium retention which serve as distinct clinical features to be targeted by specific therapies. 111 Given the diverse etiologic factors and clinical presentations of HFpEF, we advocate the use of a “matrix approach” to guide individualized therapy in HFpEF (Table 1).…”
Section: Expert Opinionmentioning
confidence: 99%
“…In HFpEF, the REDUCE LAP-HF I and II trials (randomized controlled trials of an interatrial shunt device vs. placebo sham procedure) could be viewed as enrichment trials [25]. Patients undergo non-invasive and invasive hemodynamic screening to ensure that only those patients that express the target (elevated left atrial [LA] pressure compared to right atrial [RA] pressure at rest or during exercise) are included into the trial, thereby enriching the trial for those patients who are most likely to respond to a device that creates a shunt between the LA and RA.…”
Section: Innovative Clinical Trial Designs For Hfpefmentioning
confidence: 99%